2016
DOI: 10.1021/acscatal.6b00127
|View full text |Cite
|
Sign up to set email alerts
|

(N-Heterocyclic Carbene)2-Pd(0)-Catalyzed Silaboration of Internal and Terminal Alkynes: Scope and Mechanistic Studies

Abstract: Pd(ITMe) 2 (PhCCPh) acts as a highly reactive precatalyst in the silaboration of terminal and internal alkynes to yield a number of known and novel 1-silyl-2-boryl alkenes. Unprecedented mild reaction temperatures for terminal alkynes, short reaction times, and low catalytic loadings are reported. During mechanistic studies, cis-Pd(ITMe) 2 (SiMe 2 Ph)(Bpin) was directly synthesized by oxidative addition of PhMe 2 SiBpin to Pd-(ITMe) 2 (PhCCPh). This represents a very rare example of a (silyl)(boryl)palladium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
19
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…[1] Alkyne hydrosilylation is the most atom-economic method to access such compounds. [6] Whereas several methods are available for the synthesis of vicinal borosilanes, [7] there are only few approaches towards geminal borosilanes, [8] and methods that provide access to derivatives with at etrasubstituted carbon center are particularly rare. [4] In the early 2000s,the groups of Tr ost [4a,b] and Yamamoto [4c] independently reported the Markovnikov hydrosilylation of terminal alkyl alkynes to form a-vinylsilanes with pentamethylcyclopentadiene ruthenium catalysts.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[1] Alkyne hydrosilylation is the most atom-economic method to access such compounds. [6] Whereas several methods are available for the synthesis of vicinal borosilanes, [7] there are only few approaches towards geminal borosilanes, [8] and methods that provide access to derivatives with at etrasubstituted carbon center are particularly rare. [4] In the early 2000s,the groups of Tr ost [4a,b] and Yamamoto [4c] independently reported the Markovnikov hydrosilylation of terminal alkyl alkynes to form a-vinylsilanes with pentamethylcyclopentadiene ruthenium catalysts.…”
mentioning
confidence: 99%
“…[2] One important issue in the hydrosilylation of terminal alkynes is the control of the regio-and stereochemistry because the reaction can generate (E)-b-, (Z)-b-, and a-vinylsilanes.I ndeed, although many catalysts can be used for anti-Markovnikov selective hydrosilylation to form b-vinylsilanes, [3] reactions of alkynes without ad irecting group that proceed with Markovnikov selectivity (a-selectivity) are rare. [6] Whereas several methods are available for the synthesis of vicinal borosilanes, [7] there are only few approaches towards geminal borosilanes, [8] and methods that provide access to derivatives with at etrasubstituted carbon center are particularly rare. Cossy and co-workers showed that Ru alkylidene complexes also catalyze the hydrosilylation of alkyl alkynes to form a-vinylsilanes with ah igh degree of regioselectivity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 However, even those organocatalytic diborations have been hardly applicable to acetylenedicarboxylates 7, which have been recognized as reactive substrates in related catalytic element element additions such as bis-silylation, 10 silastannation, 11 and silaboration. 12 Recently, we reported the diboration of substituted pyrazines with 1, where 4,4¤-bipyridines are effective catalysts to activate the boronboron σ bond of 1.13 This study triggered the development of diboron-based borylations by pyridine-based catalysts.14 Herein, we describe the first diboration of acetylenedicarboxylates 7 to afford 2,3-diborylfumarates in the presence of 4,4¤-bipyridine as an effective catalyst (Scheme 2).The reaction of dimethyl acetylenedicarboxylate (7a) with 1 was carried out under conditions established for the diboration of other alkynes (Entries 24, Table 1). In the presence of Pt(PPh 3 ) 4 (5 mol %), 7a underwent addition of 1 in DMF at 110°C to give 8a in a low yield as a mixture of stereoisomers (38%, E:Z = 14:86, Entry 2).…”
mentioning
confidence: 99%
“…8 However, even those organocatalytic diborations have been hardly applicable to acetylenedicarboxylates 7, which have been recognized as reactive substrates in related catalytic element element additions such as bis-silylation, 10 silastannation, 11 and silaboration. 12 Recently, we reported the diboration of substituted pyrazines with 1, where 4,4¤-bipyridines are effective catalysts to activate the boronboron σ bond of 1.…”
mentioning
confidence: 99%